Career duration in the NBA - Do foreign players exit early? - Groothuis, P. A.; Hill, J. R. (Journal of Sports Economics, 2018)
Using a panel of National Basketball Association players from 1990 through 2013, we analyze the determinants of career length in the league. We find that foreign-born players who did not play college basketball in the United States have shorter careers than do American-born players holding performance constant. Foreign-born players who played college basketball in the United States do not have shorter careers. We suggest that both push and pull immigration factors might cause this early exit.